AN INNOVATIVE APPROACH TO THE DEVELOPMENT OF MASTER PROGRAMME IN TEACHER EDUCATION - E. N. PEREVOSHCHIKOVA (Высшее образование в России)
The paper presents a new approach to the construction of Master Programme “Designing a new educational product”. The essence of the innovation is changing of the objectoriented approach typical for many Master’s programs of teacher education to the activity approach orienting students to create their own educational product. Depending on the contingent admitted to master’s programs, the article provides an example of educational product types that can serve as a target social order for the selection of the Master Programme. The changes concern also questions of organization of the educational process. Basing on the modular approach there are designed educational modules: conceptual module, design module, technological module, the diagnostic module, electronic educational module, management. These modules determine not only the structure of the educational process, but also the components of the basic professional educational programs. The article gives an example of selection of educational disciplines for educational modules. The selection is based on the planned educational outcomes. The paper also gives an example of the construction of evaluation tools for the assessment of educational outcomes.